Group Therapy in Psychiatric Patients - Thongpradab, Juthamas (Journal of The Royal Thai Army Nurses, 2020)
Psychiatric illness is an important problem which has a tendency to increase an incidence rate. Psychiatric illness are the deviate of cognitive, emotional and behavioral, it is a chronic disease, frequent relapses and have an affects on patients, families, and society. Psychiatric nurses have an important role to do the group therapy that is considered a form of psychosocial treatment, which is a role that psychiatric nurses can act independently to improve the self-care potential of psychiatric patients to be able to live peacefully in society. This article aims to present about group therapy, form of group therapy, the nature of group therapy, good characteristics of therapist, the role of leader of the group therapy, the process of group therapy, problems and solutions of group therapy and case study.